3.9k views
5 votes
8 - (3x - 2)² for x = -2

User Atevm
by
4.8k points

2 Answers

3 votes

Answer:-56

Step-by-step explanation:8 - (3*-2 - 2)^2=-56

User DrKey
by
5.4k points
2 votes

∑ Hey, asher102108 ⊃

Answer:

-56

Explanation:

Given:

8 - (3x - 2)² for x = -2

Solve:

Since it given that x = -2, we can just substitute.

Step by step below;

  • 8 - (3x - 2)²
  • = 8 - ( 3(-2) - 2)² - Substitute -2
  • = 8 - (-8)² Multiply (3(-2) - 2) = -8
  • = 8 - 64 (-8)² also know as -8× -8= -64
  • = - 56 8 - 64 = -56

Therefore the answer for the expression is -56.

xcookiex12

8/16/2022

User Fhd
by
5.0k points